Are cash transfers the right tool to get the most vulnerable into school? - Evans, David K.; Gale, Charles; Kosec, Katrina (Center for Global Development, 2020)
With increased focus on the shortfall in learning outcomes around the world (the “learning crisis”!), one might assume that just about every child is in school, or at least that every young child is in primary school. But sadly, that’s not the case: in low-income countries, just two-thirds of children complete their primary education!